Responses of Plant Reproductive Phenology to Winter-Biased Warming in an Alpine Meadow - Hu, Xiaoli; Zhou, Wenlong; Sun, Shucun (Frontiers in Plant Science, 2020)
Climate warming is often seasonally asymmetric with a higher temperature increase toward winters than summers. However, the effect of winter-biased warming on plant reproductive phenology has been seldom investigated under natural field conditions. The goal of this study was to determine the effects of winter-biased warming on plant reproductive phenologies. In an alpine meadow of Tibetan Plateau, we deployed six large (15 m × 15 m × 2.5 m height) open top chambers (three warmed chambers and three non-warmed chambers) to achieve winter-biased warming (i.e., a small increase in annual mean temperature with a greater increase towards winter than summer). We investigated three phenophases (onset and offset times and duration) for both the flowering and fruiting phenologies of 11 common species in 2017 and 8 species in 2018. According to the vernalization theory, we hypothesized that mild winter-biased warming would delay flowering and fruiting phenologies. The data indicated that the phenological responses to warming were species-specific (including positive, neutral, and negative responses), and the number of plant species advancing flowering (by averagely 4.5 days) and fruiting onset times (by averagely 3.6 days) was higher than those delaying the times. These changes were inconsistent with the vernalization hypothesis (i.e. plants need to achieve a threshold of chilling before flowering) alone, but can be partly explained by the accumulated temperature hypothesis (i.e. plants need to achieve a threshold of accumulative temperature before flowering) and/or the overtopping hypothesis (i.e. plants need to reach community canopy layer before flowering). The interspecific difference in the response of reproductive phenology could be attributed to the variation in plant traits including plant height growth, the biomass ratio of root to shoot, and seed mass. These results indicate that a mild winter-biased warming may trigger significant change in plant reproductive phenology in an alpine meadow.